Subcritical water for recycling of plastic waste (polyurethane) - Oh, Wei Hong (Nanyang Technological University, 2024)
Polyurethane (PU) represents more than 7 % of global plastic production and is widely used in our daily life such as in sofa and mattress cushion, insulation, packaging, and many more applications. The proper end-of-life handling or disposal of the PU waste has become increasingly important considering the environmental impact of plastic waste. PU foam represents about 65% of the total PU, which is one huge PU type that needs to be handled properly to ensure sustainability of the resources and environment.